(untitled) (Palíndromo, 2022)
This paper develops a reflection on how the details can reveal the symbolisms that generate meanings in the image, and how the artists represented references to other areas of the arts in the sculpture in question. The study starts from three medieval sculptures that depict the Virgin Mary and the Child Jesus and establish dialogues about the human and divine character of Mary in Christian iconology. The Marian cult had great appeal in the Middle Ages and the chosen sculptures are works that feature different styles. One sculpture represents the humanized Virgin, the other is presented as a composite reliquary, and the last is an image of the human Mary, immersed in grief.